Mobilisations collectives et femmes immigrées en France - Sylvie Thiéblemont-Dollet (Amnis)
Although quite many studies deal with immigration (more particularly that of men), the fact of tackling the problem on the angle of immigrant women and the communication processes they have developed in their host country provides Social Sciences with an essential contribution. For this reason, this article examines the collective mobilization, between 2000 and 2008, through the actions and communication processes used by several immigrant women or women from ethnic minorities, natives of Maghreb and West Africa, particularly from the example of the Ni Putes ni Soumises (“Neither whores nor submissive”) movement. On the one hand, this paper analyzes the networks of interdependence and “contagion” between these actresses with identical racial origins, as these women express a feeling of exclusion and associate their status — whether social (unemployment, poorly-qualified jobs), ethnic (North African or African origins) or spatial (suburban housing estates, suburbs, districts with tough reputation) — with the same stigma that relegates them to a discriminatory universe. On the other hand, this article brings out the specifications of their words according to where and when they were delivered, and catches their way of getting organized and their mobilizing capacities.This analysis may be read too as a suggestion that these women constitute an emergent and mutant social body. Emergent, because it is relatively recent, considering its visibility in the public sphere; and mutant, too, because it involves women who take part in a change currently intervening in French society, and who give of themselves a new image: not the image of feminists in the classical sense of the term with the connotations it carries, but one, rather, that fits in the perspective of gender behaviour, like coeducation and modalities of interaction between women and men. Finally, because after being for a long time excluded from the social and militant representation by French institutions and confined to the role of émigrés’ wives, that emergent, mutant, social body may well have this characteristic that it brings together women who care for Other People and have the will to participate actively in the city’s public actions.